PELAKSANAAN AKAD NIKAH DI KANTOR URUSAN AGAMA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA PADA SAAT PEMBATASAN SOSIAL DI MASA PANDEMI COVID-19 - Sastika, Asi; Ardiansyah, Ardiansyah; Wibowo, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
In a marriage if you want to be declared legal according to religion and state, of course it must be recorded at the local District Office of Religious Affairs (KUA) in order to have clear legality, but due to the Covid-19 outbreak, the community is hampered and the implementation is different. So that the purpose of this research is 1) Knowing what the social impacts during the covid-19 pandemic are for people who carry out contracts at the KUA, Sungai Ambawang District. 2) Knowing how to carry out the marriage contract between the guardian and the prospective groom at the KUA, Sungai Ambawang District when socializing. Using qualitative research methods, namely field research and sociological juridical approach. The data sources used primary data in the form of interviews with the head and head of the KUA Sungai Ambawang District and secondary data in the form of books, articles, journals and other documents. Data collection techniques in the form of interviews and documentation. Data collection tools using interview guidelines and soft phones. then checked for validity using source triangulation. The data analysis technique uses data reduction, data presentation and conclusion drawing. So it can be said that: 1) The social impact during the covid-19 pandemic for people who carry out the marriage contract at the KUA, Sungai Ambawang District is to minimize wedding financing because there is no reception. And when planning a festive wedding reception is on the agenda and something may not happen. And 2) the implementation of the marriage contract at the KUA, Sungai Ambawang District at the time of social registration by registering online through simkah.web. And at the time of the implementation, keep shaking hands normally, only applying health protocols and using gloves for the prospective groom and the head of the village/guardian to avoid direct transmission of COVID-19.